Targeting blood-brain-barrier transcytosis – perspectives for drug delivery. (1st July 2017) - Mäger, Imre; Meyer, Axel H.; Li, Jinghuan; Lenter, Martin; Hildebrandt, Tobias; Leparc, German; Wood, Matthew J.A.
Abstract: Efficient transcytosis across the blood-brain-barrier (BBB) is an important strategy for accessing drug targets within the central nervous system (CNS). Despite extensive research the number of studies reporting successful delivery of macromolecules or macromolecular complexes to the CNS has remained very low. In order to expand current research it is important to know which receptors are selective and abundant on the BBB so that novel CNS-targeting antibodies or other ligands could be developed, targeting those receptors for transcytosis. To do that, we have set up a proteomics- and transcriptomics-based workflow within the COMPACT project (Collaboration on the Optimization of Macromolecular Pharmaceutical Access to Cellular Targets) of the Innovative Medicines Initiative (IMI) of the EU. Here we summarise our overall strategy in endothelial transcytosis research, describe in detail the related challenges, and discuss future perspectives of these studies. This article is part of the Special Issue entitled "Beyond small molecules for neurological disorders". Highlights: Drug delivery across the blood-brain-barrier (BBB) must be achieved for respective therapies. Targeting BBB-specific receptors is promising strategy for drug delivery. Novel BBB-specific receptors can be discovered via proteomic/transcriptomic workflow. Receptor discovery workflow is challenging but risks can be minimized by careful planning.